2020
DOI: 10.1177/0894439320951765
|View full text |Cite
|
Sign up to set email alerts
|

Using Only Numeric Labels Instead of Verbal Labels: Stripping Rating Scales to Their Bare Minimum in Web Surveys

Abstract: With the increasing use of smartphones in web surveys, considerable efforts have been devoted to reduce the amount of screen space taken up by questions. An emerging stream of research in this area is aimed at optimizing the design elements of rating scales. One suggestion that has been made is to completely abandon verbal labels and use only numeric labels instead. This approach deliberately shifts the task of scale interpretation to the respondents and reduces the information given to them with an intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The number of categories and use of verbal labels are both well researched. Research based on randomized experiments has consistently shown that a moderate number of response categories (five-seven), which are all verbalized, is associated with higher reliability and validity than other realizations (e.g., Gummer and Kunz 2021;Maitland 2009aMaitland , 2009b. Researchers have also addressed the effect of rating scales on results in the context of LVM (e.g., Menold and Tausch 2016), demonstrating that seven fully verbalized categories are consistently associated with tenable or high data quality.…”
Section: Introductionmentioning
confidence: 99%
“…The number of categories and use of verbal labels are both well researched. Research based on randomized experiments has consistently shown that a moderate number of response categories (five-seven), which are all verbalized, is associated with higher reliability and validity than other realizations (e.g., Gummer and Kunz 2021;Maitland 2009aMaitland , 2009b. Researchers have also addressed the effect of rating scales on results in the context of LVM (e.g., Menold and Tausch 2016), demonstrating that seven fully verbalized categories are consistently associated with tenable or high data quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent developments in graphical user interfaces have raised the possibility of greater use of VAS in web-based survey applications [30][31][32][33]. Furthermore, a mobile device or multi-device on a web-based survey has been addressed [34,35].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“… Weigold et al (2021) examined four item formats—horizontal radio button, text box, drop-down menu, and vertical radio button—and generally found both quantitative and qualitative equivalence across formats. Several studies have examined the effects of altering response option labels (e.g., only using verbal labels for the end points of the scale or removing verbal labels altogether; Gummer & Kunz, 2021 ; Spratto et al, 2021 ; Steinberg & Rogers, in press ). The findings of this research generally support using verbal labels for each level of the response option continuum.…”
mentioning
confidence: 99%